1995
DOI: 10.1017/s0022112095000309
|View full text |Cite
|
Sign up to set email alerts
|

Boundary layer flow of air over water on a flat plate

Abstract: A non-similar boundary layer theory for air blowing over a water layer on a flat plate is formulated and studied as a two-fluid problem in which the position of the interface is unknown. The problem is considered at large Reynolds number (based on x), away from the leading edge. We derive a simple non-similar analytic solution of the problem for which the interface height is proportional to x1/4 and the water and air flow satisfy the Blasius boundary layer equations, with a linear profile in the water and a Bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 4 publications
1
44
0
Order By: Relevance
“…The iterative procedure ensures convergence of the interface height and velocity profiles at every downstream location, ξ . The solution at large ξ agrees with the asymptotic behaviour described in Nelson et al (1995) and provides the mean profile for the numerical evaluation of the continuous-spectrum modes.…”
Section: The Two-fluid Theoretical Formulationsupporting
confidence: 75%
“…The iterative procedure ensures convergence of the interface height and velocity profiles at every downstream location, ξ . The solution at large ξ agrees with the asymptotic behaviour described in Nelson et al (1995) and provides the mean profile for the numerical evaluation of the continuous-spectrum modes.…”
Section: The Two-fluid Theoretical Formulationsupporting
confidence: 75%
“…The continuity of the streamwise velocity then yieldŝ 12) with the shape of the interface f (x) determined byλ + f 2 = const, as follows from the mass conservation within the film; cf. Nelson et al (1995). 14) hold, similar to the usual triple-deck solution but with the extra contribution U 01 in the horizontal velocity and, more significantly for buoyant fluids, with the vertical pressure variation of order ε 0 .…”
Section: Derivation Of the Viscous/inviscid Interaction Equationsmentioning
confidence: 57%
“…Then the steady boundary layer unaffected by instabilities can be treated as predominantly independent of the film flow; see e.g. Nelson et al (1995). In the bulk of the boundary layer, where the vertical coordinate y 1 = yε −4 0 is of O (1), the velocity components and pressure can be written in the form…”
Section: Derivation Of the Viscous/inviscid Interaction Equationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, sidewall friction and water setup caused by wind shear may reduce the effective surface flow. Nelson et al 39 formulated a nonsimilar analytic solution for laminar airflow shearing over a thin water layer on a flat plate. The solution showed that the height of the surface film was proportional to x 1/4 and the surface current calculated using their method is only about 0.14% of the free-stream velocity.…”
Section: -11mentioning
confidence: 99%